Composite precursor, composite positive electrode material, secondary battery, and electric device

By using the inner core and outer layer structure of the composite precursor in the positive electrode material, the surface alkalinity and moisture absorption and deterioration of the lithium supplement agent are reduced, the air stability is improved, and the problem of degradation of the existing lithium supplement agents is solved. Improves the overall performance of the secondary battery.

CN119219061APending Publication Date: 2024-12-31HUAWEI TECH CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202310794650.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-29
Publication Date
2024-12-31

AI Technical Summary

Technical Problem

The existing positive electrode lithium supplement agent has too high surface alkalinity and poor air stability, resulting in damage to material binder, jelly decomposition, film decomposition and degradation of battery performance.

Method used

Using a composite precursor, the inner core and outer adhesion layer are both metal oxides. Through the selection of metal elements in different valence states, the inner core and the active elements are combined to form active element-rich substances. The outer adhesion layer reduces the active element content and forms a higher air Stable lithium supplement.

Benefits of technology

It effectively reduces the surface alkalinity of lithium supplement agents, avoids damage to the binder, improves air stability, enhances the lithium supplement effect, and improves the overall performance of the secondary battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119219061A_ABST
    Figure CN119219061A_ABST
Patent Text Reader

Abstract

The invention provides a composite precursor, a composite positive electrode material, a secondary battery and electric equipment. The composite precursor comprises an inner core and an outer attaching layer arranged on at least part of the surface of the inner core, and the inner core and the outer attaching layer are both metal oxides or substances capable of being decomposed to form the metal oxides. The composite precursor and the active elements are chemically combined through selection of metal elements with different valence states in the inner core and the outer attachment layer, so that the substance of the inner core forms an active element-rich substance, and the substance of the outer attachment layer forms a positive electrode active substance; after the composite precursor is compounded with the active elements, the mole number of the active elements in each mole of the inner core material is larger than that of the active elements in each mole of the outer attachment layer material. The composite precursor can reduce the surface alkalinity of the lithium supplement agent and improve the air stability, so that the first-circle charging specific capacity of the secondary battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery materials, and specifically to a composite precursor, a composite positive electrode material, a secondary battery and an electrical device. Background Art

[0002] Using high-capacity silicon-oxygen / silicon-carbon and other negative electrode materials to replace graphite is an effective means to improve the energy density of batteries. However, the first efficiency of silicon-based negative electrodes is low (usually around 70-80%), and when paired with conventional positive electrodes (such as LiCoO2, around 94-97%), it will result in a larger first-cycle irreversible capacity. This problem can be effectively solved by lithium replenishment. Lithium replenishment methods can be roughly divided into two types: negative electrode lithium replenishment and positive electrode lithium replenishment. Positive electrode lithium replenishment is widely used because of its strong process compatibility, convenient operation, and easy industrialization. The existing positive electrode lithium replenishment technology route is mainly achieved by adding sacrificial positive electrode active materials, that is, releasing a large amount of active lithium during the first charging process, thereby providing additional lithium ions to the battery system to make up for the different coulomb first efficiencies of the positive and negative electrodes and the consumption of lithium sources during the formation of the SEI film.

[0003] At present, the cathode lithium supplement additives that have been studied more and have great commercial potential are mainly lithium-rich transition metal oxides (such as Li2NiO2, Li6CoO4, Li5FeO4, etc.). However, existing lithium supplements usually have problems such as excessive surface alkalinity and poor air stability (easy to absorb moisture and deteriorate). Among them, excessive surface alkalinity will destroy the binder in the slurry, causing abnormal conditions such as jellying of the slurry and coating delamination; and moisture absorption and deterioration will not only lead to a decrease in the lithium supplement effect, but also affect the moisture control in the process of battery cell manufacturing, affecting the overall performance of the battery. Summary of the invention

[0004] The present application provides a composite precursor, a composite positive electrode material, a secondary battery and an electrical device to reduce the surface alkalinity of a lithium supplement and improve air stability.

[0005] In a first aspect, the present application provides a composite precursor for synthesizing a positive electrode material, comprising a core and an outer layer disposed on at least a portion of the surface of the core, wherein the core and the outer layer are both metal oxides or substances that can be decomposed to form metal oxides, and the core and the outer layer are selected by metal elements of different valence states so that the composite precursor and the active material compound are used to form an active element-rich substance in the core, and the outer layer is used to form a positive electrode active material;

[0006] After the composite precursor is combined with the active element, the molar number of the active element in each mole of the core material is greater than the molar number of the active element in each mole of the outer layer material.

[0007] The composite precursor of the present application has a core and an outer layer, and both the core and the outer layer are metal oxides or substances that can decompose to form metal oxides. After the composite precursor is combined with the active element, since the core contains more active elements, taking lithium-ion batteries as an example, when making positive electrode materials, the core can form lithium supplement materials, and the outer layer can form positive electrode active materials. The reduction in the content of active elements in the outer layer can alleviate the problem of excessive alkalinity on the surface of the material to a certain extent, avoid the contact of the core with the electrolyte after the lithium supplement agent is formed, and reduce the damage of the lithium supplement agent with excessive alkalinity to the binder in the positive electrode material layer. At the same time, the setting of the outer layer can also serve as a protective layer for the core, avoiding direct contact with the air after the core forms the lithium supplement agent, so that the formed lithium supplement agent has better air stability and alleviates the negative impact caused by moisture absorption and deterioration.

[0008] The active element is an element that can be reversibly intercalated and deintercalated in the positive electrode active material, such as lithium, sodium, potassium, calcium, etc.

[0009] In an optional implementation, the molecular formula of the kernel is N c Y d The molecular formula of the outer layer is M a X b ,in:

[0010] N is selected from at least one of Co, Mn, Fe, Ni, Cr, Cu, V, Nb and Zr;

[0011] M is selected from at least one of Co, Mn, Fe, Ni, Ti, Cr, Cu and V;

[0012] X, Y are each independently selected from at least one of O, OH, OOH, and CO3;

[0013] 1≤a≤5, 1≤b≤5, 1≤c≤5, 1≤d≤5.

[0014] When X is selected from O, the metal oxide formed by it and M, when used as the outer layer material, can directly react with the active element to form the positive electrode active material of the composite positive electrode material. When Y is selected from O, the metal oxide formed by it and N, when used as the core material, can directly react with the active element to form the active element supplement of the composite positive electrode material.

[0015] In an optional implementation, when the M and the N are selected from the same metal, the M a X b The valence of M is greater than that of N c Y dThus, the oxide of N can combine with more active elements to form an inner core with a high content of active elements. The oxide of M can combine with a lower amount of active elements relative to N to form an outer layer with a low content of active elements.

[0016] In an optional implementation, the outer layer is a continuous outer layer or a discontinuous outer layer, the continuous outer layer covers the entire surface of the inner core, and the discontinuous outer layer covers part of the surface of the inner core in a dispersed manner. The outer layer can cover the inner core in various forms, including full covering, half covering, or island covering.

[0017] In an optional implementation, the core is a single-particle structure or a multi-particle structure. When the core is a single-particle structure, the outer layer can be a full coating layer, a half coating layer or a dispersed island coating layer. When the core is a multi-particle structure, the outer layer can be a full coating layer.

[0018] In an optional implementation, the thickness of the outer layer is 0.1 nm-0.1 μm, preferably 0.1 nm-50 nm, and more preferably 5 nm-15 nm. The thickness of the outer layer is limited to the above range, which can achieve effective coating of the inner core.

[0019] In an optional implementation, the material forming the inner core may include at least one of metal oxides, metal hydroxides, metal oxyhydroxides or metal salts. The metal oxide forming the inner core includes at least one of NiO, CoO, MnO, CuO, Fe2O3, Cr2O3, Fe3O4, Cr3O4, ZrO2, V2O5 or Nb2O5. The metal hydroxide forming the inner core includes at least one of Ni(OH)2, Co(OH)2, Mn(OH)2 or Cu(OH)2. The metal oxyhydroxide forming the inner core includes at least one of FeOOH or CrOOH; the metal salt forming the inner core includes at least one of NiCO3, CoCO3, MnCO3, CuCO3, Zr(CO3)2, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2, CuCO3·Cu(OH)2 or Zr CO3(OH)2.

[0020] In an optional implementation, the material forming the outer layer may include at least one of metal oxides, metal hydroxides, metal oxyhydroxides or metal salts. The metal oxide forming the outer layer includes at least one of CuO, Ni2O3, Co2O3, Mn2O3, Fe2O3, Cr2O3, Co3O4, Mn3O4, Fe3O4, Ni3O4, Cr3O4, TiO2, MnO2 or V2O5. The metal hydroxide forming the outer layer includes at least one of Ni(OH)2, Co(OH)2, Mn(OH)2, Cu(OH)2, V(OH)2, Al(OH)3, Fe(OH)3, Cr(OH)3, V(OH)3, Ti(OH)4. The metal oxyhydroxide forming the outer layer includes at least one of NiOOH, CoOOH, MnOOH, FeOOH, CrOOH and VOOH. The metal salt forming the outer layer includes at least one of NiCO3, CoCO3, MnCO3, CuCO3, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2 or CuCO3·Cu(OH)2.

[0021] In a second aspect, the present application provides a composite positive electrode material, which is prepared using the composite precursor of the present application, wherein in the composite precursor, a substance in the form of a metal oxide is combined with an active element to form the composite positive electrode material; or, a composite precursor that can be decomposed to form a metal oxide is sintered and combined with an active element to obtain the composite positive electrode material;

[0022] In the composite positive electrode material, the number of moles of active elements in each mole of the core material is greater than the number of moles of active elements in each mole of the outer layer material.

[0023] In a third aspect, the present application provides a secondary battery comprising a positive electrode plate, wherein the positive electrode plate comprises a positive electrode collector and a positive electrode material layer coated on at least one side surface of the positive electrode collector, wherein the positive electrode material layer comprises the composite positive electrode material of the present application.

[0024] In a fourth aspect, the present application provides an electrical device, which includes the secondary battery of the present application.

[0025] The technical effects that can be achieved by the second to fourth aspects mentioned above can be described with reference to the corresponding effects in the first aspect mentioned above, and will not be repeated here.

[0026] Among them, the data in the above-mentioned possible implementation methods of the present application, such as the thickness of the outer layer and other data, when measuring, the values ​​within the scope of engineering measurement error should be understood to be within the scope specified in the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 A schematic diagram of the structure of a composite precursor according to an embodiment;

[0028] Figure 2 is a schematic structural diagram of a composite precursor of another embodiment;

[0029] Figure 3 is a schematic diagram of the structure of another composite precursor;

[0030] Figure 4 This is a SEM photo of the CoCO3 seed crystal in Example 1;

[0031] Figure 5 This is the X-ray diffraction pattern of LiCoO2@Li6CoO4 powder material;

[0032] Figure 6 This is the transmission electron microscope photo of LiCoO2@Li6CoO4 powder;

[0033] Figure 7 It is a comparison chart of the first cycle charging specific capacity of the secondary batteries of Examples 1-2 and Comparative Example 1.

[0034] Reference numerals:

[0035] 11- inner core; 12- outer layer. DETAILED DESCRIPTION

[0036] In order to make the objectives, technical solutions and advantages of the present application clearer, the present application will be further described in detail below in conjunction with the accompanying drawings.

[0037] The terms used in the following embodiments are only for the purpose of describing specific embodiments and are not intended to be limiting of the present application. As used in the specification and appended claims of the present application, the singular expressions "a", "an", "above", "the" and "this" are intended to also include expressions such as "one or more", unless there is a clear contrary indication in the context.

[0038] References to "one embodiment" or "some embodiments" etc. described in this specification mean that a particular feature, structure or characteristic described in conjunction with the embodiment is included in one or more embodiments of the present application. Thus, the phrases "in one embodiment", "in some embodiments", "in some other embodiments", "in some other embodiments", etc. that appear at different places in this specification do not necessarily refer to the same embodiment, but mean "one or more but not all embodiments", unless otherwise specifically emphasized in other ways. The terms "including", "comprising", "having" and their variations all mean "including but not limited to", unless otherwise specifically emphasized in other ways.

[0039] Existing lithium supplements are usually lithium-rich compounds, which have too high surface alkalinity and poor air stability, and are easy to affect the overall performance of secondary batteries. The core-shell structured lithium supplement is usually a lithium-rich compound coated with a protective layer to protect the lithium-rich compound. The preparation method of the existing lithium supplement is to directly coat the surface of the lithium-rich compound with other lithium compounds. High-temperature sintering is usually required during the coating process to achieve the combination of the two. The lithium-rich compound usually produces by-products during the sintering process, thereby reducing the lithium supplement performance of the lithium supplement.

[0040] To solve the above problems, an embodiment of the present application provides a composite precursor for synthesizing a composite positive electrode material. The composite precursor includes an inner core and an outer layer arranged on at least a portion of the surface of the inner core. The inner core and the outer layer are both metal oxides or substances that can decompose to form metal oxides. The inner core and the outer layer are selected by metal elements of different valence states to make the composite precursor and the active element combine, so that the material of the inner core forms a material rich in active elements, and the material of the outer layer forms a positive electrode active material. After the composite precursor is combined with the active element, the number of moles of active elements in each mole of the inner core material is greater than the number of moles of active elements in each mole of the outer layer material.

[0041] When the precursor is used to prepare a composite positive electrode material, it can be first sintered and then reacted with active elements to form a positive electrode material rich in active elements. Since the sintering process is first performed and then reacted with active elements, the formation of by-products during the sintering process can be reduced.

[0042] Among them, the active element can be an active ion that can shuttle back and forth between the positive electrode material and the negative electrode material in the secondary battery, and an ion that can be reversibly deintercalated in the positive electrode material. In lithium-ion batteries, the active element is lithium ion. In sodium-ion batteries, the active element is sodium ion. In calcium-ion batteries, the active element is calcium ion. In magnesium-ion batteries, the active element is magnesium ion. The above is only an exemplary description of the active element. In other types of secondary batteries, the active element can also be an ion of the corresponding type.

[0043] The structure and composition of the composite precursor of the present application are further described in detail below in conjunction with the accompanying drawings. Figure 1 FIG. 1 is a schematic diagram of the structure of a composite precursor of an embodiment. Figure 1 As shown, the composite precursor includes a core 11 and an outer layer 12 coated on the surface of the core 11. Figure 1 In the illustrated embodiment, the outer layer 12 is a continuous outer layer 12, which covers the entire surface of the inner core 11 to form a continuous coating layer. Figure 2 FIG. 1 is a schematic diagram of the structure of a composite precursor of another embodiment. Figure 1 and Figure 2 As shown, the core 11 can be a single particle structure or a multi-particle structure. The single particle structure can be a single crystal particle. The multi-particle structure can be a plurality of primary particles agglomerated to form secondary particles. Figure 3 Figure 2 is a schematic diagram of the structure of another composite precursor. Figure 3 As shown, in an optional embodiment, the outer layer 12 is a discontinuous outer layer 12. At least part of the surface of the core 11 is not coated by the outer layer 12. The outer layer 12 of the discontinuous structure can form an island-shaped coating structure with the core 11. That is, the discontinuous outer layer 12 is dispersedly attached to the surface of the core 11.

[0044] Refer to Figures 1 to 3 The thickness of the outer layer 12 may be 0.1 nm-0.1 μm, preferably 0.1 nm-50 nm, and more preferably 5 nm-15 nm. For example, the thickness of the outer layer 12 may be 0.1 nm, 0.2 nm, 0.5 nm, 1 nm, 10 nm, 20 nm, 30 nm, 50 nm, 70 nm, 80 nm, 90 nm, or 100 nm.

[0045] The composite precursor of the embodiment of the present application has a molecular formula of N c Y d The molecular formula of the outer layer 12 is M a X b Wherein: N is selected from at least one of Co, Mn, Fe, Ni, Cr, Cu, V, Nb or Zr; M is selected from at least one of Co, Mn, Fe, Ni, Ti, Cr, Cu or V; X, Y are each independently selected from at least one of O, OH, OOH, CO3; 1≤a≤5, 1≤b≤5, 1≤c≤5, 1≤d≤5.

[0046] Wherein, N and M are both metal elements. Y and X can be O element, or other elements or element combinations that can form metal compounds with metals. c Y d And outer layer 12M a X bAfter sintering treatment, they can all be converted into metal oxides, which can form gas exclusion with elements. After sintering, both the inner core 11 and the outer attached layer 12 form metal oxides to avoid the influence of other elements on the performance of the subsequently formed composite cathode material.

[0047] In the inner core 11 and the outer attached layer 12, M and N can be the same metal or different metals. When M and N are the same metal, their valences are different, and the valence of M can be greater than the valence of N, so that in the composite cathode material finally formed by combining with the active element, the active element contained in the inner core 11 is greater than the active element contained in the outer attached layer 12. When M and N are different metals, in the composite cathode material finally formed by combining with the active element, the active element contained in the inner core 11 is greater than the active element contained in the outer attached layer 12.

[0048] As can be seen from the above, the material forming the inner core 11 can include at least one of substances such as metal oxides, metal hydroxides, metal hydroxyoxides or metal salts. Among them, the metal oxides forming the inner core 11 include MO (M = Cu), M2O3 (M = Ni, Co, Mn, Fe, Cr), M3O4 (M = Co, Mn, Fe, Ni, Cr) or MO2 (M = Ti, Mn), M2O5 (M = V) or a combination of one or more of them;示例性地, including but not limited to at least one of NiO, CoO, MnO, CuO, Fe2O3, Cr2O3, Fe3O4, Cr3O4, ZrO2, V2O5 or Nb2O5.

[0049] The metal hydroxides forming the inner core 11 include M(OH)2 (M = Ni, Co, Mn, Cu, V), M(OH)3 (M = Fe, Cr, V), M(OH)4 (M = Ti), (Ni x Co y Mn 1-x-y (OH)2 (0 < x < 1, 0 < y < 1), Ni x Co y Al 1-x-y (OH)2 (0 < x < 1, 0 < y < 1), M 1-y-z-p-q M' y M” z M”' p M”” q (OH)2 (0 < y < 1, 0 ≤ z < 1, 0 ≤ p < 1, 0 ≤ q < 1; M / M' / M” / M”” / M”” = Ni, Co, Mn, Fe, Ti, Cu, V, Cr) or a combination of one or more of them;示例性地, including but not limited to at least one of Ni(OH)2, Co(OH)2, Mn(OH)2 or Cu(OH)2.

[0050] The metal oxyhydroxide forming the core 11 includes a combination of MOOH (M=Ni, Co, Mn, Fe, Cr, V); illustratively, includes at least one of FeOOH and CrOOH.

[0051] The metal salt forming the inner core 11 includes a combination of one or more of MCO3 (M=Ni, Co, Mn, Cu), MCO3·M(OH)2 (M=Ni, Co, Mn, Cu), and illustratively includes but is not limited to at least one of NiCO3, CoCO3, MnCO3, CuCO3, Zr(CO3)2, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2, CuCO3·Cu(OH)2 or Zr CO3(OH)2.

[0052] The material forming the outer layer 12 may include at least one of metal oxides, metal hydroxides, metal oxyhydroxides or metal salts. The metal oxide forming the outer layer 12 includes one or more combinations of MO (M = Ni, Co, Mn, Cu), M2O3 (M = Fe, Cr), M3O4 (M = Fe, Cr) or MO2 (M = Zr), M2O5 (M = V, Nb); illustratively, including but not limited to at least one of CuO, Ni2O3, Co2O3, Mn2O3, Fe2O3, Cr2O3, Co3O4, Mn3O4, Fe3O4, Ni3O4, Cr3O4, TiO2, MnO2 or V2O5.

[0053] The metal hydroxide forming the outer layer 12 includes a combination of M(OH)2 (M=Ni, Co, Mn, Cu); exemplary pairs include but are not limited to at least one of Ni(OH)2, Co(OH)2, Mn(OH)2, Cu(OH)2, V(OH)2, Al(OH)3, Fe(OH)3, Cr(OH)3, V(OH)3, and Ti(OH)4.

[0054] The metal oxyhydroxide forming the outer layer 12 includes a combination of one or more MOOH (M=Fe, Cr); illustratively, it includes but is not limited to at least one of NiOOH, CoOOH, MnOOH, FeOOH, CrOOH, and VOOH.

[0055] The metal salts forming the outer coating layer 12 include one or more combinations of MCO3 (M = Ni, Co, Mn, Cu), M(CO3)2 (M = Zr), MCO3·M(OH)2 (M = Ni, Co, Mn, Cu), and MCO3(OH)2 (M = Zr). Exemplarily, it includes at least one of NiCO3, CoCO3, MnCO3, CuCO3, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2, or CuCO3·Cu(OH)2.

[0056] Based on the same technical concept, an embodiment of the present application provides a composite cathode material. The composite cathode material is prepared from the composite precursor of the present application. Among them, the substance in the form of metal oxide combines with the active element to form the composite cathode material; or, the composite precursor capable of decomposing to form metal oxide is sintered and combined with the active element to obtain the composite cathode material. The composite cathode material of the present application retains the core-shell structure of the composite precursor. Among them, in the composite cathode material, the number of moles of the active element per mole of the inner core substance is greater than the number of moles of the active element per mole of the outer coating layer substance.

[0057] Among them, the inner core 11 part in the composite cathode material can be used as an active element supplement. In a lithium-ion battery, the inner core 11 can be used as a lithium supplement agent. In a sodium-ion battery, the inner core 11 can be used as a sodium supplement agent.

[0058] Taking the lithium-ion cathode material as an example, in the composite cathode material, the compounds formed by the outer coating layer 12 can be one or more combinations of LiCoO2, LiNiO2, LiMnO2, LiNi x Co y Mn 1-x-y O2, LiNi x Co y Al 1-x-y O2; where 0 < x < 1 and 0 < y < 1. The compounds formed by the inner core 11 include one or more combinations of Li3VO4, Li2MnO2, Li3NbO4, Li5FeO4, Li6CoO4, Li2NiO2, Li2CuO2, and Li8ZrO6.

[0059] Taking the sodium-ion cathode material as an example, in the composite cathode material, the compounds formed by the outer coating layer 12 are NaMO2 (M = Ni, Co, Mn, Fe, Ti, Cu, V, Cr), Na x M 1-y-z-p-q M' y M” z M”' p M”” qOne or more combinations of O2 (0 < x ≤ 1, 0 < y < 1, 0 ≤ z < 1, 0 ≤ p < 1, 0 ≤ q < 1; M / M' / M” / M”” / M”” = Ni, Co, Mn, Fe, Ti, Cu, V, Cr). The compounds formed by the core 11 include one or more combinations of Na6CoO4, Na5FeO4, Na6MnO4, Na5CrO4, and Na4NiO3.

[0060] The following will further elaborate on the composite precursor of the present application in combination with specific examples and comparative examples.

[0061] Example 1

[0062] Composite precursor CoOOH + Co(OH)2@CoCO3

[0063] Step S11: Prepare CoCO3 seeds: Weigh industrial-grade cobalt chloride raw materials and prepare a cobalt chloride solution with a molar concentration of 2.0 mol / L. Weigh industrial-grade sodium carbonate raw materials and prepare a sodium carbonate solution with a molar concentration of 2.0 mol / L. Add 8 L of the cobalt chloride solution to a 50 L stainless steel reactor, turn on the stirring device, and add deionized water to adjust the ionic concentration of Co 2+ to 0.04 mol / L. Control the reaction temperature at 40 °C, and simultaneously pump in the cobalt chloride and sodium carbonate solutions. Use an online pH control system to keep the pH of the solution in the reactor within the range of 8.0 - 8.5. React at a constant temperature for 24 h.

[0064] Step S12: After removing the supernatant, centrifuge and separate, wash the precipitate three times each with deionized water and absolute ethanol, and dry it in a blast drying oven at 90 °C for 4 h to obtain CoCO3 seeds.

[0065] Step S13: Deposit a layer of Co(OH)2 on the surface of the CoCO3 seeds. Weigh industrial-grade cobalt nitrate raw materials and prepare a cobalt nitrate solution with a cobalt concentration of 20 g / L. Take an ammonia water solution with an ammonia concentration of 20 g / L and mix it with a sodium hydroxide solution with a concentration of 200 g / L at a volume ratio of 0.1:1, denoted as solution A. First, add the CoCO3 seeds to the reactor, and then add the cobalt nitrate solution and solution A in a co-current manner for reaction, and turn on the stirring device. During the reaction, strictly control the pH value at 8.4 and the temperature at 75 °C, and react at a constant temperature for 48 h. After the reaction, the suspension contains CoCO3 (Co(OH)2@CoCO3) seeds with Co(OH)2 precipitated on the surface.

[0066] Step S14: Surface micro-oxidation. For the suspension that has completely reacted in step S13, under the premise of turning on the stirring device, introduce a nitrogen-oxygen mixed gas with a low oxygen content, and the flow rate is 0.8 m 3 / h, and the reaction lasts for 10 hours. After the reaction is completed, Co(OH)2 on the surface of CoCO3 will produce CoOOH through micro-oxidation, forming a thin coating layer.

[0067] Step S15, remove the supernatant and centrifuge, wash the precipitate three times with deionized water and anhydrous ethanol, and dry it in a 90° C. forced air oven for 4 hours to obtain a composite precursor CoOOH+Co(OH)2@CoCO3.

[0068] SEM photos of CoCO3 seed crystals are shown in Figure 4 As shown in (a) to (c), (a) to (c) are SEM images at different magnifications. The SEM images of Co(OH)2@CoCO3) seeds are shown in Figure 4 As shown in (d) to (f), (d) to (f) are SEM images at different magnifications. Figure 4 As shown in (g) to (i), (g) to (i) are SEM images at different magnifications. Figure 4 As shown, from CoCO3 to Co(OH)2@CoCO3 and then to CoOOH+Co(OH)2@CoCO3, there is an obvious morphological change on the particle surface, indicating that an outer layer is formed on the surface of the inner core.

[0069] During the above reaction process, the valence states of cobalt elements obtained by X-ray photoelectron spectroscopy analysis of the powder materials at each stage are listed in Table 1. From the data in Table 1, it can be seen that after surface micro-oxidation of Co(OH)2@CoCO3, a small amount of cobalt element (2.93%) is converted from divalent to trivalent.

[0070] Table 1

[0071]

[0072] Composite cathode materials

[0073] Step S21, placing the CoOOH+Co(OH)2@CoCO3 powder in an argon atmosphere of a muffle furnace, and sintering at 780° C. for 15 h to obtain Co2O3@CoO powder.

[0074] Step S22, Co2O3@CoO and Li2O were weighed at a molar ratio of 3:1, and ball-milled for 6 hours. Then, the mixture was reacted at 600° C. in an argon atmosphere for 12 hours to obtain a core-shell structured LiCoO2@Li6CoO4 powder, in which the LiCoO2 coating layer was relatively thin.

[0075] Figure 5 This is the X-ray diffraction pattern of LiCoO2@Li6CoO4 powder material. Figure 6This is a transmission electron microscope photo of LiCoO2@Li6CoO4 powder. Figure 5 As shown in Figure 1, when the LiCoO2 coating layer is thin, the X-ray diffraction spectrum does not show obvious LiCoO2 characteristic peaks, but is dominated by Li6CoO4 characteristic peaks. Figure 6 Transmission electron microscope photos show that there is an obvious coating layer on the surface of the particles with a thickness of about 10nm, and the coating layer has a clear and regular lattice structure, corresponding to the layered characteristics of LiCoO2.

[0076] Secondary battery preparation

[0077] After LiCoO2@Li6CoO4 was placed in the air for 0, 1, 2, 4, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0078] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0079] Example 2

[0080] Composite precursor CoOOH@Co(OH)2:

[0081] Step S11, prepare Co(OH)2 seed crystals. Weigh industrial-grade cobalt nitrate raw materials and prepare a cobalt nitrate solution with a cobalt concentration of 20 g / L. Take an ammonia solution with an ammonia concentration of 20 g / L, and mix it with a sodium hydroxide solution with a concentration of 200 g / L at a volume ratio of 0.1:1, and record it as solution A. In a reactor, add the cobalt nitrate solution and solution A in parallel to react, and turn on the stirring device. During the reaction, the pH value is strictly controlled to be 8.4 and the temperature is 75°C, and the reaction is carried out at a constant temperature for 48 hours. After the reaction is completed, the suspension contains Co(OH)2 seed crystals.

[0082] Step S12: Surface strong oxidation. For the suspension that has been completely reacted in (1), a nitrogen-oxygen mixed gas with a low oxygen content is introduced with a flow rate of 0.8 m 3 / h, and react for 10 hours. After the reaction is completed, the surface of the Co(OH)2 particles will produce CoOOH through strong oxidation, forming a thick coating layer.

[0083] Step S13, remove the supernatant and centrifuge, cross-wash the precipitate with deionized water and anhydrous ethanol three times each, and dry it in a 90° C. forced air oven for 4 hours to obtain the composite metal compound precursor CoOOH@Co(OH)2.

[0084] During the above reaction, the cobalt valence states obtained by X-ray photoelectron spectroscopy analysis of the powder materials at each stage are listed in Table 2. As shown in Table 2, after strong surface oxidation, the cobalt element (25.3%) with a relatively high content in the powder material is converted from divalent to trivalent.

[0085] Table 2

[0086]

[0087] Composite cathode materials

[0088] Step S21, placing the CoOOH@Co(OH)2 powder in an argon atmosphere of a muffle furnace, and sintering at 780°C for 15 hours to obtain Co2O3@CoO powder.

[0089] Step S21, Co2O3@CoO and Li2O were weighed at a molar ratio of 3:1, and ball-milled for 6 hours. Then, the mixture was reacted at 600° C. in an argon atmosphere for 12 hours to obtain a core-shell structured LiCoO2@Li6CoO4 powder, in which the LiCoO2 coating layer was relatively thick.

[0090] The X-ray diffraction pattern of the powder material is shown in Figure 5 Since the LiCoO2 coating layer generated under this condition is relatively thick, the X-ray diffraction pattern shows a relatively strong LiCoO2 characteristic peak.

[0091] Secondary battery preparation

[0092] After LiCoO2@Li6CoO4 was placed in the air for 0, 1, 2, 4, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0093] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0094] Comparative Example 1

[0095] Precursor CoCO3

[0096] Step S11: Preparation of CoCO3 seed crystals

[0097] Weigh industrial-grade cobalt chloride raw materials and prepare a cobalt chloride solution with a molar concentration of 2.0 mol / L. Weigh industrial-grade sodium carbonate raw materials and prepare a sodium carbonate solution with a molar concentration of 2.0 mol / L. Add 8 L of cobalt chloride solution to a 50 L stainless steel reactor, turn on the stirring device, and add deionized water to adjust the Co2+ The ion concentration is 0.04 mol / L. The reaction temperature is controlled at 40°C, and cobalt chloride and sodium carbonate solutions are pumped in at the same time. The pH of the solution in the reactor is maintained in the range of 8.0-8.5 through an online pH control system, and the reaction is carried out at a constant temperature for 24 hours.

[0098] Step S12, remove the supernatant and centrifuge, wash the precipitate three times with deionized water and anhydrous ethanol, and dry it in a 90° C. forced air oven for 4 hours to obtain CoCO3 powder.

[0099] Positive electrode lithium supplement material

[0100] Step S21, CoCO3 powder is placed in an argon atmosphere in a muffle furnace and sintered at 780° C. for 15 hours to obtain CoO powder.

[0101] Step S22, CoO and Li2O were weighed in a molar ratio of 3:1, and ball-milled for 6 hours, and then reacted at 600° C. in an argon atmosphere for 12 hours to obtain Li6CoO4 powder.

[0102] The X-ray diffraction pattern of the powder material is shown in Figure 5 . Figure 5 The X-ray diffraction pattern of Comparative Example 1 shows the characteristic peak of Li6CoO4 with higher purity.

[0103] Secondary battery preparation

[0104] After Li6CoO4 was placed in the air for 0, 1, 2, 4, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0105] The positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and electrochemical tests were performed.

[0106] The first cycle charge specific capacity of Examples 1-2 and Comparative Example 1 were tested respectively, and the test results are as follows: Figure 7 As shown. Figure 7 As shown, after the surface coating, the stability of the lithium supplement Li6CoO4 in the air of the composite positive electrode material of Example 1-2 is greatly improved, so the first cycle charging specific capacity that can be released after being placed in the air for a long time is significantly increased.

[0107] Example 3

[0108] Composite precursor NiOOH+Ni(OH)2@NiCO3·Ni(OH)2:

[0109] Step S11: preparing NiCO3·Ni(OH)2 seed crystals

[0110] Weigh industrial-grade nickel sulfate raw materials and prepare a nickel sulfate solution with a molar concentration of 2.0 mol / L. Weigh industrial-grade sodium carbonate raw materials and prepare a sodium carbonate solution with a molar concentration of 2.0 mol / L. Pump cobalt chloride and sodium carbonate solution into a 50L stainless steel reactor at the same time, adjust the flow rate of sodium carbonate solution to 5-1000L / h, the flow rate of nickel sulfate solution to 50-1000L / h, and turn on the stirring device. Control the reaction temperature to 80°C, and maintain the pH of the solution in the reactor in the range of 8.0-8.3 through an online pH control system, and react at a constant temperature for 24 hours.

[0111] Step S12, remove the supernatant and centrifuge, wash the precipitate three times with deionized water and anhydrous ethanol, and dry it in a 90° C. forced air oven for 4 hours to obtain NiCO3·Ni(OH)2 seed crystals.

[0112] Step S13: precipitate a layer of Ni(OH)2 on the surface of the NiCO3·Ni(OH)2 seed crystal

[0113] Weigh industrial-grade nickel sulfate raw materials and prepare a nickel sulfate solution with a concentration of 5.0 mol / L. Weigh industrial-grade cobalt sulfate raw materials and prepare a cobalt sulfate solution with a concentration of 5.0 mol / L. The above two solutions are mixed, in which the molar ratio of cobalt ions to nickel ions is 1:100, recorded as solution B. Take an ammonia solution with an ammonia concentration of 20 g / L and mix it with a sodium hydroxide solution with a concentration of 200 g / L at a volume ratio of 0.1:1. First, add NiCO3·Ni(OH)2 seeds to the reactor, then add B solution for reaction, and turn on the stirring device. During the reaction, the pH value is strictly controlled to be 11 and the temperature is 55°C, and the reaction is kept at a constant temperature for 12 hours. After the reaction is completed, the suspension contains NiCO3·Ni(OH)2 seeds with Ni(OH)2 precipitated on the surface.

[0114] Step S14: surface micro-oxidation.

[0115] For the suspension that has been completely reacted in step S13, a nitrogen-oxygen mixed gas with a low oxygen content is introduced with a flow rate of 1.0 m 3 / h, and the reaction lasts for 6 hours. After the reaction is completed, Ni(OH)2 on the surface of NiCO3·Ni(OH) will produce NiOOH through micro-oxidation, forming a thin coating layer.

[0116] Step S15, remove the supernatant and centrifuge, cross-wash the precipitate with deionized water and anhydrous ethanol three times each, and dry it in a 90° C. forced air oven for 4 hours to obtain the composite metal compound precursor NiOOH+Ni(OH)2@NiCO3·Ni(OH)2.

[0117] Cathode Materials

[0118] Step S21, placing NiOOH+Ni(OH)2@NiCO3·Ni(OH)2 powder in an argon atmosphere of a muffle furnace, and sintering at 780° C. for 15 h to obtain Ni2O3@NiO powder.

[0119] Step S22, weigh Ni2O3@NiO and Li2O in a molar ratio of 3:2, respectively, and ball-mill for 6 hours. Then, react in an argon atmosphere at 600° C. for 24 hours to obtain a core-shell structured LiNiO2@Li2NiO2 powder, wherein the LiNiO2 coating layer is relatively thin.

[0120] Secondary battery preparation

[0121] After LiNiO2@Li2NiO2 was placed in the air for 0, 2, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0122] The above positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed. The results are shown in Table 3.

[0123] Example 4

[0124] Composite precursor NiOOH@Ni(OH)2

[0125] Step S11: preparing Ni(OH)2 seed crystals

[0126] Weigh industrial-grade nickel sulfate raw materials and prepare a nickel sulfate solution with a concentration of 5.0 mol / L. Weigh industrial-grade cobalt sulfate raw materials and prepare a cobalt sulfate solution with a concentration of 5.0 mol / L. The above two solutions are mixed, in which the molar ratio of cobalt ions to nickel ions is 1:100, recorded as solution B. First, add an ammonia solution with an ammonia concentration of 20 g / L to the reactor, and mix it with a sodium hydroxide solution with a concentration of 200 g / L at a volume ratio of 0.1:1, then add solution B to react, and turn on the stirring device. During the reaction, the pH value is strictly controlled to be 11 and the temperature is 55°C, and the reaction is kept at a constant temperature for 12 hours. After the reaction is completed, the suspension contains Ni(OH)2 seeds.

[0127] Step S12: Surface strong oxidation. In step S11, the suspension that has been completely reacted is introduced into a nitrogen-oxygen mixed gas with a low oxygen content at a flow rate of 1.0 m 3 / h, and the reaction lasts for 6 hours. After the reaction is completed, the surface of Ni(OH)2 particles will produce NiOOH through strong oxidation, forming a thick coating layer.

[0128] Step S12, remove the supernatant and centrifuge, cross-wash the precipitate with deionized water and anhydrous ethanol three times each, and dry it in a 90° C. forced air oven for 4 hours to obtain the composite metal compound precursor NiOOH@Ni(OH)2.

[0129] Composite cathode materials

[0130] Step S21, placing NiOOH@Ni(OH)2 powder in an argon atmosphere of a muffle furnace, and sintering at 780°C for 15 hours to obtain Ni2O3@NiO powder.

[0131] Step S22, weigh Ni2O3@NiO and Li2O in a molar ratio of 3:2, ball mill for 6 hours, and then react in an argon atmosphere at 600°C for 24 hours to obtain a core-shell structured LiNiO2@Li2NiO2 powder, wherein the LiNiO2 coating layer is relatively thick.

[0132] Secondary battery preparation

[0133] After LiNiO2@Li2NiO2 was placed in the air for 0, 2, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0134] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0135] Comparative Example 2

[0136] Precursor NiCO3·Ni(OH)2

[0137] Step S11: preparing NiCO3·Ni(OH)2 seed crystals

[0138] Weigh industrial-grade nickel sulfate raw materials and prepare a nickel sulfate solution with a molar concentration of 2.0 mol / L. Weigh industrial-grade sodium carbonate raw materials and prepare a sodium carbonate solution with a molar concentration of 2.0 mol / L. Pump cobalt chloride and sodium carbonate solution into a 50L stainless steel reactor at the same time, adjust the flow rate of sodium carbonate solution to 5-1000L / h, and the flow rate of nickel sulfate solution to 50-1000L / h, and turn on the stirring device. Control the reaction temperature to 80°C, and maintain the pH of the solution in the reactor in the range of 8.0-8.3 through an online pH control system. React at a constant temperature for 24 hours, and the suspension contains NiCO3·Ni(OH)2.

[0139] Step S12, remove the supernatant and centrifuge, wash the precipitate three times with deionized water and anhydrous ethanol, and dry it in a 90° C. forced air oven for 4 hours to obtain NiCO3·Ni(OH)2 powder.

[0140] Cathode Materials

[0141] NiCO3·Ni(OH)2 powder was placed in a muffle furnace in an argon atmosphere and sintered at 780℃ for 15h to obtain NiO powder. NiO and Li2O were weighed separately at a molar ratio of 3:2 and ball-milled for 6h. Then, the mixture was reacted in an argon atmosphere at 600℃ for 24h to obtain Li2NiO2 powder with a core-shell structure.

[0142] Secondary battery preparation

[0143] After Li2NiO2 was placed in the air for 0, 2, 8, and 24 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0144] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0145] The first cycle charging specific capacity of the secondary batteries of Examples 3-4 and Comparative Example 2 was tested, and the test results are listed in Table 3.

[0146] Table 3

[0147]

[0148] It can be seen from Table 3 that after the surface coating, the stability of the lithium supplement Li2NiO2 in the air of the composite positive electrode material of Example 3-4 is greatly improved, so the first cycle charging specific capacity that can be released after being placed in the air for a long time is significantly increased.

[0149] Example 5

[0150] Composite precursor MnCO3@Fe2O3

[0151] Step S11, weighing industrial-grade manganese sulfate raw material, preparing a manganese sulfate solution with a concentration of 0.5 mol / L. Weighing industrial-grade ammonium bicarbonate raw material, preparing an ammonium bicarbonate solution with a concentration of 2.0 mol / L. In a reactor, first add industrial-grade nano-Fe2O3 powder, then add manganese sulfate solution, turn on the stirring device, and then add ammonium bicarbonate solution at a speed of 10 ml / min to react. Continue stirring for 6 hours and then stand overnight, and the suspension contains MnCO3@Fe2O3.

[0152] Step S12, remove the supernatant and centrifuge, cross-wash the precipitate with deionized water and anhydrous ethanol three times each, and dry it in a 90° C. forced air oven for 4 hours to obtain the composite metal compound precursor MnCO3@Fe2O3.

[0153] Composite cathode materials

[0154] Step S21, placing the MnCO3@Fe2O3 powder in an air atmosphere of a muffle furnace, and sintering at 780° C. for 15 hours to obtain Mn2O3@Fe2O3 powder.

[0155] Step S22, weigh Mn2O3@Fe2O3 and Li2O in a molar ratio of 3:1, ball mill for 6 hours, and then react at 600°C in an argon atmosphere for 24 hours to obtain LiMnO2@Li5FeO4 powder with a core-shell structure.

[0156] Secondary battery preparation

[0157] After LiMnO2@Li5FeO4 was placed in the air for 0, 6, and 12 hours, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on an aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0158] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0159] Comparative Example 3

[0160] Preparation of secondary batteries with lithium supplement Li5FeO4

[0161] Fe2O3 and Li2O were weighed in a molar ratio of 3:1, ball-milled for 6 h, and then reacted at 600 °C in an argon atmosphere for 24 h to obtain Li5FeO4 powder.

[0162] After Li5FeO4 was placed in the air for 0, 6, and 12 hours respectively, it was uniformly mixed with the conductive agent Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 8:1:1. The slurry was coated on the aluminum foil current collector and then dried, rolled, and cut to obtain the positive electrode sheet.

[0163] The above-mentioned positive electrode sheet was matched with the lithium sheet, and a half-cell was assembled with 1M LiPF6+EC / EMC / DMC (1:1:1, v / v / v) as the electrolyte, and an electrochemical test was performed.

[0164] The first cycle charging specific capacity of the secondary batteries of Example 5 and Comparative Example 2 were tested, and the test results are listed in Table 4.

[0165] Table 4

[0166]

[0167] It can be seen from the test data in Table 4 that after the surface coating, the stability of the lithium supplement Li5FeO4 in the air of the positive electrode material of Example 5 is greatly improved, so the first cycle charging capacity that can be released after being placed in the air for a long time is significantly increased.

[0168] In summary, the positive electrode composite material can be formed by in-situ reaction using a composite precursor, which can reduce the occurrence of side reactions. The composite positive electrode material of the embodiment of the present application can be used as a lithium supplement additive. The core structure can be used as a lithium supplement, and the outer layer can be used as a positive electrode active material. In addition, the composite positive electrode material of the embodiment of the present application can still release a high lithium supplement capacity after being placed in the air for a long time, thereby improving the first-cycle charging capacity of the secondary battery. It shows that the composite positive electrode material of the present application has high air stability.

[0169] The above embodiments are only exemplary descriptions, wherein the active element may be other active elements besides lithium, such as sodium. Other active elements will not be described in detail here, but the composite precursor of the embodiment of the present application may also be used with other types of active element compounds for use in corresponding secondary batteries.

[0170] The above are only specific implementations of the present application, but the protection scope of the present application is not limited thereto. Any technician familiar with the technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.

Claims

1. A composite precursor for synthesizing a positive electrode material, characterized in that: It comprises an inner core and an outer layer arranged on at least part of the surface of the inner core, wherein the inner core and the outer layer are both metal oxides or substances that can be decomposed to form metal oxides, and the inner core and the outer layer are selected by metal elements of different valence states so that the composite precursor is combined with active elements to form active element-rich substances in the inner core, and the substances in the outer layer form positive electrode active substances; After the composite precursor is combined with the active element, the molar number of the active element in each mole of the core material is greater than the molar number of the active element in each mole of the outer layer material.

2. The composite precursor according to claim 1, characterized in that The molecular formula of the core is N c Y d The molecular formula of the outer layer is M a X b ,in: N is selected from at least one of Co, Mn, Fe, Ni, Cr, Cu, V, Nb and Zr; M is selected from at least one of Co, Mn, Fe, Ni, Ti, Cr, Cu and V; X, Y are each independently selected from at least one of O, OH, OOH, and CO3; 1≤a≤5, 1≤b≤5, 1≤c≤5, 1≤d≤5.

3. The composite precursor according to claim 1 or 2, characterized in that: When the M and the N are selected from the same metal, the M a X b The valence of M is greater than that of N c Y d Compounds containing N.

4. The composite precursor according to any one of claims 1 to 3, characterized in that: The outer layer is a continuous outer layer or a discontinuous outer layer. The continuous outer layer covers the entire surface of the inner core, and the discontinuous outer layer covers part of the surface of the inner core in a dispersed manner.

5. The composite precursor according to any one of claims 1 to 4, characterized in that: The thickness of the outer layer is 0.1 nm-0.1 μm.

6. The composite precursor according to any one of claims 1 to 5, characterized in that: The material forming the inner core includes at least one of NiO, CoO, MnO, CuO, Fe2O3, Cr2O3, Fe3O4, Cr3O4, ZrO2, V2O5, Nb2O5, Ni(OH)2, Co(OH)2, Mn(OH)2, Cu(OH)2, FeOOH, CrOOH, NiCO3, CoCO3, MnCO3, CuCO3, Zr(CO3)2, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2, CuCO3·Cu(OH)2, and Zr CO3(OH)2.

7. The composite precursor according to any one of claims 1 to 6, characterized in that: The substances forming the outer layer include at least one of CuO, Ni2O3, Co2O3, Mn2O3, Fe2O3, Cr2O3, Co3O4, Mn3O4, Fe3O4, Ni3O4, Cr3O4, TiO2, MnO2, V2O5, Ni(OH)2, Co(OH)2, Mn(OH)2, Cu(OH)2, V(OH)2, Al(OH)3, Fe(OH)3, Cr(OH)3, V(OH)3, Ti(OH)4, NiOOH, CoOOH, MnOOH, FeOOH, CrOOH, VOOH, NiCO3, CoCO3, MnCO3, CuCO3, NiCO3·Ni(OH)2, CoCO3·Co(OH)2, MnCO3·Mn(OH)2 or CuCO3·Cu(OH)2.

8. A composite positive electrode material, characterized in that: In the composite precursor according to any one of claims 1 to 7, the substance in the form of a metal oxide is combined with an active element to form the composite positive electrode material; or, the composite precursor that can be decomposed to form a metal oxide is sintered and combined with an active element to obtain the composite positive electrode material; In the composite positive electrode material, the number of moles of active elements in each mole of the core material is greater than the number of moles of active elements in each mole of the outer layer material.

9. A secondary battery, characterized in that: It comprises a positive electrode plate, wherein the positive electrode plate comprises a positive electrode current collector and a positive electrode material layer coated on at least one side surface of the positive electrode current collector, wherein the positive electrode material layer comprises the composite positive electrode material as claimed in claim 8.

10. An electrical device, characterized in that: Comprising the secondary battery as claimed in claim 9.

Citation Information

Cited By

  • Substance containing non-lithium metal element and preparation method therefor

    WO2026144875A1